LASER OXYGEN ISOTOPE ANALYSIS OF SILICATE/OXIDE GRAIN SEPARATES: EVIDENCE FOR A GRAIN SIZE EFFECT? - Fouillac A.M.; Girard J.P. (My University, 1996)
285 oxygen isotope analyses of grain separates of quartz, biotite, muscovite, aegirine, actinolite, olivine and chromite were carried out by laser fluorination using BrF5. Two of the eleven samples analyzed are oxygen isotope standards (NBS-28 and NBS-30) with internationally agreed δ18O-values. The δ18O-values of all other samples were previously determined by conventional fluorination. Laser oxygen isotope analyses were performed on chips, calibrated size separates and powdered aliquots of each sample. The results indicate that fine-grained (< 250 μm) and powdered samples of most minerals yield laser δ18O-values that are systematically and reproducibly lower than the conventional δ18O-values. A continuous series of five size fractions, ranging from > 500 to < 75 μm, was analyzed for two quartz samples. The results show a progressive decrease of laser δ18O-values with decreasing grain size. The δ18O-value of the finest size fraction is, on average, 0.8–1.0‰ lower than the conventionally measured δ18O-value. Also, 22 analyses of quartz standard NBS-28, which grain size is 120–250 μm, yielded an average laser δ18O-value of +8.8 ± 0.2‰, i.e. 0.8‰ lower than its true value. Similarly, powdered aliquots (grain size < 75 μm) of all minerals but actinolite and aegirine gave laser δ18O-values that were 0.5–2.0‰ lower than conventional values. For all minerals, except muscovite and chromite, laser analyses of size fractions > 250 μm yielded correct δ18O-values, suggesting that the grain size of 250 μm may constitute a threshold. Detailed examination of the data indicates that this unexpected depletion cannot be attributed to contamination during powdering, loss of material during fusion (low yields), intragrain heterogeneity of the samples, atmospheric contamination, oxygen isotope fractionation during the fluorination reaction or during the O2CO2 conversion. In addition, laser beam size, which is shown to have, an influence on the laser δ18O-values measured for some minerals, is not responsible for the observed depletion. At this time, we do not have a complete understanding of the cause(s) of the observed grain size effect. As a consequence, it is advisable that investigators performed preliminary tests before analyzing fine-grained or powdered minerals by the laser fluorination technique.